Building technology report. Building services / Mohd. Nazam Md. Kassim - Md. Kassim, Mohd. Nazam (Faculty of Architechture , Planning & Surveying, 1982)
The building technology report is a brief report based on various references. It is governed by and will discuss the basic principles of mechanical services in the building, with particular attention to water supply, and sanitation and plumbing systems each with its specified function in a complex mechanism. It also briefly discusses the aspects of design and space requirements.